Effects of mirabegron on JJ stent‐related symptoms: A multicentric study. Issue 2 (4th December 2020) - Cinar, Onder; Tanidir, Yiloren; Ozer, Selcuk; Cizmeci, Sezer; Erbatu, Oguzcan; Ozdemir, Turan; Girgin, Reha; Ongun, Sakir; Ucer, Oktay; Kizilay, Fuat; Sen, Volkan; Irer, Bora; et al.
Abstract: Aims of the study: To investigate the effect of mirabegron 50 mg/daily for JJ stent‐related symptoms after ureteroscopic stone surgery. Methods: Medical records of 145 patients who were given a single daily oral dose of 50 mg of mirabegron for relieving stent‐related symptoms were retrospectively analysed. Demographic and clinical data and stone parameters were recorded. All participants completed the Turkish version of the Ureter Symptom Score Questionnaire (USSQ‐T) on the postoperative 7th day, and again after at least 3 weeks, before JJ stent removal. The severity of stent‐related symptoms was statistically compared before and after the mirabegron treatment. Results: The mean urinary symptoms score decreased significantly from 30.87 ± 9.43 to 22.61 ± 6.78 ( P < .0001), mean body pain score decreased significantly from 21.82 ± 11.22 to 14.03 ± 7.52 ( P < .0001), mean work performance score decreased from 10.50 ± 8.61 to 7.02 ± 6.51 ( P < .0001) and mean general health score decreased significantly from 15.43 ± 6.50 to 11.12 ± 3.70 ( P < .0001). The mean sexual matters score significantly decreased from 3.88 ± 3.40 to 2.48 ± 2.03 ( P < .0001), the additional problem score decreased from 9.31 ± 4.61 to 6.51 ± 2.83 ( P < .0001) and the overall quality of life (QoL) score decreased from 5.18 ± 1.94 to 4.23 ± 1.71 after mirabegron use ( P < .0001). Conclusion: Daily use of 50 g of mirabegron significantly improved stent‐related symptoms, sexual matters and quality of life.